PON Virtualisation with EAST-WEST Communications for Low-Latency Converged Multi-Access Edge Computing (MEC) - Ruffini, Marco (My University, 2020)
We propose a virtual-PON based Mobile Fronthaul (MFH) architecture that allows direct communications between edge points (enabling EAST-WEST communication). Dynamic slicing improves service multiplexing while supporting ultra-low latency under 100ms between cells and MEC nodes.
Optical Fibre Communications (OFC)
PUBLISHED
Keywords: Cloud Radio Access Network (C-RAN); Quality of service; Passive optical networks; 5G networks